TANGGUNG JAWAB AHLI WARIS NOTARIS YANG MENINGGAL DUNIA TERHADAP PROTOKOL NOTARIS DI KAITKAN DENGAN KEPASTIAN HUKUM NOTARIS PEMEGANG PROTOKOL - Syauqi, Alfa; Erny Kencanawati; Yudha Cahya Kumala (Journal of Innovation Research and Knowledge, 2025)
In carrying out their duties, a Notary is guided by the rules inherent in the Notary's Office, as stipulated in the Notary Law and other related regulations. A Notary is a public official obligated to maintain and guarantee the accuracy of the Notary's protocol. When a Notary dies, the protocol must be handed over to another Notary to receive it to ensure its certainty. However, this protocol often raises issues due to unfinished work or lawsuits regarding the deceased Notary's protocol. The research problem is formulated as follows: How are the responsibilities of the deceased Notary's heirs and their obligations regarding the Notary's protocol regulated? And what is the legal certainty of the deceased Notary's protocol for the Notary receiving the protocol? The legal theories applied as analytical tools are Hans Kelsen's theory of responsibility and Gustav Radbruch's theory of legal certainty. The method used in this research is a normative juridical research type, namely library legal research or tertiary data. The writing approaches used are the statutory approach, the conceptual approach, the analytical approach, and the case approach. The legal material collection technique was carried out by identifying and inventorying positive legal regulations, books, journals, and other legal sources. The legal material analysis technique employed grammatical interpretation, systematic interpretation, and legal construction methods. The research findings indicate that the heirs of a deceased notary are responsible for submitting the notary's protocol to the notary receiving the protocol through the Regional Supervisory Board and are responsible for other matters related to the protocol. To ensure legal certainty for the responsible heirs and the notary who assists the heirs in resolving any issues that arise, regulations governing this matter are necessary.